PENGARUH PENERAPAN MODEL PEMBELAJARAN QUANTUM LEARNING DAN QUANTUM TEACHING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA - Andriani Fatimah; Ulfiani Rahman; Andi Ika Prasasti (JURNAL PUSAKA : Media Kajian dan Pemikiran Islam, 2019)
This study discusses the comparison of the application of Quantum Learning and Quantum Teaching models to the ability to understand mathematical concepts of class VIII students of Wahdah Islamiyah Makassar Middle School IT. This study aims to (1) determine the students' understanding of mathematical concepts taught by applying the Quantum Learning model; (2) knowing the ability to understand the mathematical concepts of students taught by applying the Quantum Teaching model; (3) knowing the significant difference between the ability to understand mathematical concepts through the application of the Quantum Learning model with the Quantum Teaching model. The approach of this research is quantitative with the type of Quasi Experiment with the design of Nonequivalent Control Group Design. The sample in this study were students of Class VIII B2 and Class VIII B3 which were 60 people out of the total number of students of class VIII 120 people. The research instrument used was a matter of testing the ability to understand mathematical concepts, observation sheets and documentation. Data were analyzed by descriptive statistical analysis and inferential statistics. The results showed that: (1) the ability to understand the mathematical concepts of students taught by applying the Quantum Learning model had increased; (2) the ability to understand the mathematical concepts of students taught by applying Quantum Teaching models has increased; (3) there is a significant difference between the ability to understand mathematical concepts through the application of the Quantum Learning model with the Quantum Teaching model.